2001
DOI: 10.1116/1.1347048
|View full text |Cite
|
Sign up to set email alerts
|

High density diffusion barrier of ionized metal plasma deposited Ti in Al–0.5%Cu/Ti/SiO2/Si structure

Abstract: The Ti layer deposited by ionized metal plasma deposition technique and the reacted region between Ti and Al-0.5%Cu, in Al-0.5%Cu/Ti/SiO 2 /Si structure, were characterized by scanning transmission electron microscopy ͑STEM͒ and Rutherford backscattering spectroscopy ͑RBS͒. The results indicate that the Ti layer with a column-like structure grew epitaxially in the close-packed ͓001͔ direction. This growth mechanism resulted in a high-density Ti layer in Al-0.5%Cu/Ti/SiO 2 /Si structure. This epitaxially grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…This means that the Ti film texture impacts and controls the Al film texture formation, which is consistent with the work of others. 5,6,8 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that the Ti film texture impacts and controls the Al film texture formation, which is consistent with the work of others. 5,6,8 …”
Section: Resultsmentioning
confidence: 99%
“…Later, it was found that ionized physical vapor deposition (I-PVD) can improve Al(111) texture furthermore. 5,6,8 The higher energy and density of Ti plasma in the I-PVD method bring denser Ti films with fewer gas atoms and voids. 5 In this work, we studied single Ti films and Al films on TiN and Ti underlayers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] In this context, the mechanisms of self-diffusion in Ti 3 Al have been proposed by Mishin and Herzigh. [12] From experiments on impurity diffusion in Ti 3 Al, it has been found that elements with a comparatively small atomic radius (r) such as Fe (r = 0.127 nm) and Ni (r = 0.125 nm) exhibit fast diffusion by the dissociative diffusion mechanism where they pass through the interstitial octahedral sites, whereas elements with a relatively large atom size such as Nb (r = 0.147 nm) and Ga (r = 0.141 nm) exhibit relatively low diffusivity. [7] However, the diffusion of impurity atoms in intermetallic compounds depends not only on the size of the impurity atoms but also on the impurity sitesubstitution behavior.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Recently, Ti 3 Al has attracted attention for possible use as a conductive diffusion barrier in microelectronics devices such as ferroelectric random access memories. [3][4][5] Therefore, diffusion data of elements contained in integrated circuits are increasingly important. Ru¨sing et al [6] have measured self-diffusivity of Ti and interdiffusivity in binary Ti 3 Al.…”
Section: Introductionmentioning
confidence: 99%